The Memoirs of Jacques Casanova de Seingalt, Vol. IV (of VI), "Adventures In The South" : The First Complete and Unabridged English Translation, Illustrated with Old Engravings - Casanova, Giacomo, 1725-1798; Machen, Arthur, 1863-1947 (Salt Lake City, UT : Project Gutenberg, 2012)
"The Memoirs of Jacques Casanova de Seingalt, Vol. IV (of VI), Adventures In$1! =(B" by Giacomo Casanova is an autobiography written between 1789 and 1798. This volume forms part of Casanova's sprawling memoir recounting his adventures as an 18th-century Venetian libertine. Written in French across 3,500 pages, the work chronicles his remarkable life through 1774. For over a century, readers knew only censored versions translated through German. The original manuscript, rescued from wartime bombings and eventually acquired by France's National Library, reveals the unexpurgated story of one of history's most notorious adventurers. (This is an automatically generated summary.)s
Wikipedia page about this book: https://en.wikipedia.org/wiki/Histoire_de_ma_vie
Release date is 2012-03-29
Produced by David Widger
Keywords: Casanova, Giacomo, 1725-1798; Europe -- History -- 18th century -- Biography